THE NETWORKED INFORMATION ENVIRONMENT: IMPLICATIONS FOR EDUCATION OF LIBRARY AND INFORMATION PROFESSIONAL - Malhan, I.V.; Rao, Shivarama (Malaysian Journal of Library and Information Science, 2006)
Library and information science (LIS) educators are facing a major challenge in view of steady shift from communication of information on printed page to transfer of information through electronic documents. With the development of the Internet, a new pattern of organization of information emerged where documents containing electronic information are hyperlinked instead of the traditional hierarchical order of arrangement of such information. Contents of desired information are now directly accessible to users over a network of computers. These developments will not diminish the role of information professionals but offer them immense opportunities provided they are imparted the need based and state-of-the-art library and information education and training and properly and timely prepared for their new roles. This paper highlights the education and training needs of information professionals in view of the growing use of the Internet in various types of libraries and information centres.